INNOVATIVE LEGAL APPROACHES FOR ADDRESSING IMMIGRATION CRISES: THE ROLE OF INTERNATIONAL NGOS (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2024)
International non-governmental organizations (NGOs) are crucial in responding to immigration crises, offering innovative legal strategies to enhance refugee protection and support. This article delves into various legal strategies employed by international NGOs, highlighting best practices, case studies, and the influence of international legal frameworks. Through detailed analysis, the article provides insights into how these strategies address the multifaceted challenges of refugee crises and offers recommendations for improving NGO interventions in the future.